IMPACT OF PASSION AND EMOTIONAL REACTIONS TO SUCCESS AND FAILURE AMONG ATHLETES - Rabia Asghar; Saadia Hassan; M. Farhan Tabassum; Yasmeen Tabassum; Rabia Karim; Saman; Ayesha Qudus (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
This study has been aimed to examine the relationship and impact of passion and emotional reactions to success and failure among athletes of national and international athletes who participated in the 33rdNational Games in Peshawar, Pakistan. Passion and emotional reactions have a high positive correlation (r = 0.651) with significance (p = 0.002) in success. The passion and emotional reactions regarding failure are highly positively correlated (r = 0.792) with each other having significant value (p = 0.016). A simple linear regression was calculated to predicted emotional reactions based on their passion in the case of success and failure. A significant regression equation was found (F (1,74)),p < 0.018 with an R2 of 0.423. Participants predicted emotional reactions is equal to 2.855 + 0.143 passion, participants average emotional reaction increased 0.143 regarding passion in the case of success. A significant regression equation was found (F (1,74)), p < 0.000 with an R2 of 0.264. Participants predicted emotional reactions is equal to 2.065 + 0.352 passion, participants average emotional reaction increased 0.352 regarding passion in the case of failure. Finally, we conclude that passion in failure has a dominant effect on emotional reactions.An athlete must have the ability to embed and adapt with the condition, whenever it is good or failing. This study recommended that government and sports federations should arrange psychological and physical training sessions accordingly